Sistem Pendiagnosa Kerusakan Pada Motor Menggunakan Metode Case-Base Reasoning Approach - Jevan Nelson; Septian Dicky Chandra (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2019)
This paper proposes one of approach for diagnosing faults in motorcycle by using Case-Based Reasoning Approach (CBR). CBR process through four stages consist of Retrieve, Reuse, Revise and Retain. The calculation of equation have been done by Simple Matching Coefficient (SMC). Diagnosing faults in motorcycle was started by tracking initial indication that occur in the motorcycle, then ended when the solution has been found with similar of existing case. The result shown that the most often problem after diagnosis was the machine unable to start/difficult to turn on with the Carburetor Attribute Weight achieve the highest percentage of attributes. Keyword: CBR, Diagnosis, Motorcycle, SMC